Alginate vs. Hyaluronic Acid as Carriers for Nucleus Pulposus Cells: A Study on Regenerative Outcomes in Disc Degeneration - Shota Ogasawara; Jordy Schol; Daisuke Sakai; Takayuki Warita; Takano Susumu; Yoshihiko Nakamura; Kosuke Sako; Shota Tamagawa; Erika Matsushita; Hazuki Soma; Masato Sato; Masahiko Watanabe (Cells)
Intervertebral disc degeneration is a leading cause of chronic low back pain, affecting millions globally. Regenerative medicine, particularly cell-based therapies, presents a promising therapeutic strategy. This study evaluates the comparative efficacy of two biomaterials—hyaluronic acid (HA) and alginate—as carriers for nucleus pulposus (NP) cell transplantation in a beagle model of induced disc degeneration. NP cells were isolated, cultured, and injected with either HA or alginate into degenerated discs, with saline and non-cell-loaded carriers used as controls. Disc height index, T2-weighted MRI, and histological analyses were conducted over a 12-week follow-up period to assess reparative outcomes. Imaging revealed that both carrier and cell-loaded treatments improved outcomes compared to degenerative controls, with cell-loaded carriers consistently outperforming carrier-only treated discs. Histological assessments supported these findings, showing trends toward extracellular matrix restoration in both treatment groups. While both biomaterials demonstrated reparative potential, HA showed greater consistency in supporting NP cells in promoting disc regeneration. These results underscore HA’s potential as a superior carrier for NP cell-based therapies in addressing disc degeneration.